Determinan Akuntan Publik dalam Memberikan Opini Audit Going Concern pada Perusahaan Jasa Sub Sektor Transportasi di Bei Periode 2019-2021 - Fitrawansyah Fitrawansyah; Ade Irawan; Udin Saepudin; Inggil Rahmawati (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the company's financial condition and debt default on the going concern audit opinions on transportation service companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This type of research is a quantitative research using secondary data that can be accessed from the personal website of a transportation sub-sector service company listed on the Indonesia Stock Exchange (IDX). This research uses the purposive sampling method, namely by taking samples from the population based on certain criteria. The research sample based on the criteria amounted to 12 companies with a research period of 3 years, so a total sample of 36 companies' financial statement data. The data analysis method used in this study is a statistical method using logistic regression equations. Data analysis begins with processing data with Microsoft Excel, then logistic regression testing is carried out using SPSS version 23 software. The results of this study indicate that the company's financial condition affects the going concern audit opinion; Debt default does not affect the going concern audit opinion; The company's financial condition and debt default simultaneously affect the going concern audit opinion.